Needs Assessment & Identification of Opportunities : Fishery Assistance Report - Anderson, Annie-May (Coasters Association, 2004)
Funds were received from the Department of Fisheries and Oceans to assess the needs and identify the opportunities of the fishers and plant workers affected by the closure of the crab in Zone 13, and the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon. With the moratorium imposed on the cod and the closure of the snow crab fishery, the fishers and plant workers were consulted to obtain their views, which will provide a working tool for long term planning for the Coasters Association, Fishermen’s Committees, Municipalities, and Government officials. The first phase of the fishery project began on January 12th, 2004, and finished on May 29th, 2004. The second phase began on May 31st, 2004, and finished on October 1st, 2004. The objective of the project was to identify the issues, opportunities, and the individual needs ofthe fishers and plant workers affected by the closure of the crab in Zone 13, and inshore fishers affected by the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon.

Through the Looking Glass : A Comparison of Broadcast License Fees in Canada, Australia, the United Kingdom and the United States - Cox, Kirwan (2004)
The decision of a domestic broadcaster to commission a program from a producer, and the license fee paid by the broadcaster to that producer, is the foundation of the independent television production system in Canada. Most public funding for Canadian programming follows on the basis of these transactions. Unfortunately, that public funding is oversubscribed, and the production industry is chronically underfunded. Some suggest that part of this problem is the size of the Canadian broadcast license fee. Based on anecdotal evidence, it is argued that Canadian license fees are low by international standards. The purpose of this study is to see if Canadian license fees for English independent television programs are indeed low based on selected international and historical comparisons. If they are, why?